Lociranje bralca ali kaj naj storimo z možem s klobukom? - Towheed, Shafquat (Primerjalna književnost, 2011)
Using images of readers and textual sources, this essay explains the methodological basis for the Reading Experience Database and international partners. It shows how the RED projects can combine quantitative and qualitative data to locate and recover the experiences of readers through history.
Keywords: zgodovina branja; branje; bralne navade; bralna kultura; Velika Britanija; 19./20.st.; likovne upodobitve; empirične raziskave